Factors Influencing Employee Motivation: A Case Study of Padma Kanya Multiple Campus in Kathmandu - Shrestha, Rohit Kumar (Tribhuvan University Journal, 2021)
Motivation is the set of forces that make employees willing to behave in an organization. It is a crucial function of management or human resource management. The study’s objectives are to determine employees’ motivating factors as well as to identify employees’ general attitudes towards existing motivational factors. The qualitative research method was used. Primary data were collected adopting focus group discussion, observation, and interviews. Administrative and unranked employees of Padma Kanya Multiple Campus (PKMC) were selected for study by applying the case study method. Thematic analysis of data was applied. The most important motivating factor for both temporary administrative and unranked employees (helpers in office) was job security followed by pay and overtime remuneration. Administrative employees, to great extent, need intrinsic rewards particularly recognition, responsibility, promotion, and fairness whereas unranked permanent employees also, to some extent, were influenced by intrinsic factors such as recognition, equality, fairness. A different motivating factor may apply to different levels of employees in terms of their needs and desires. The general attitude of the research participants regarding motivation seems to be poor. So, both extrinsic and extrinsic factors should be improved.